Penanganan DamPak Perkembangan Pariwisata Dalam asPek lingkungan Fisik, sosial, ekonomi Dan buDaya bali (suatu tinjauan Pustaka) - Anak Agung bagus wirateja (STIMI Handayani Denpasar, 2014)
Bali region has become the main tourism destination in Indonesiabecause Bali has a unique culture background. Bali culture which major society isHindu has put the togetherness in all aspect through their daily life. Instead of theculture aspect, the nature factor is also support the tourism development, so the goalof the goverment can be reached. The culture tourism which is become priority inBali is considered be able to get devisa as wished by the goverment, because of thelimited natural resources (oil and forest). It is hoped that the society will be morecreative, so everytime can rise a new culture creativity. Finally the tourism problemin Bali will never stop forever